Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Solve for [tex] t [/tex].

[tex]\[ \frac{6}{t-4}=\frac{6}{3t+4} \][/tex]

If there is no solution, enter "no solution".

[tex] t = \boxed{} [/tex]


Sagot :

To solve the equation

[tex]\[ \frac{6}{t-4} = \frac{6}{3t+4} \][/tex]

we need to find the value of [tex]\( t \)[/tex] that satisfies this equation. Let's go through the steps to solve this step-by-step.

1. Cross-Multiply to Eliminate the Fractions:
[tex]\[ 6(3t + 4) = 6(t - 4) \][/tex]

2. Distribute the Constant across the Parentheses:
[tex]\[ 18t + 24 = 6t - 24 \][/tex]

3. Move All [tex]\( t \)[/tex]-Terms to One Side of the Equation:
Subtract [tex]\( 6t \)[/tex] from both sides:
[tex]\[ 18t - 6t + 24 = 6t - 6t - 24 \][/tex]
Simplifies to:
[tex]\[ 12t + 24 = -24 \][/tex]

4. Isolate the [tex]\( t \)[/tex]-Term:
Subtract 24 from both sides:
[tex]\[ 12t + 24 - 24 = -24 - 24 \][/tex]
Simplifies to:
[tex]\[ 12t = -48 \][/tex]

5. Solve for [tex]\( t \)[/tex]:
Divide both sides by 12:
[tex]\[ t = \frac{-48}{12} \][/tex]
Which simplifies to:
[tex]\[ t = -4 \][/tex]

So the solution to the equation

[tex]\[ \frac{6}{t-4} = \frac{6}{3t+4} \][/tex]

is:
[tex]\[ t = -4 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.